Combining explosive and high-resistance training improves performance in cyclists - Paton, C. D.; Hopkins, W. G. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
In several recent studies well-trained athletes experienced substantial gains in sprint and endurance performance when explosive strength training (e.g. Paavolainen et al., 1999) or high-intensity interval training (e.g. Osteras et al., 2002) was added to their program. Here we report the effect of combining these two types of training on performance. Methods We randomised 18 road cyclists to an experimental (n=9) or control (n=9) group for 4-5 wk of training during the competitive phase of a season. The experimental group replaced part of their usual training with 12 30-min sessions consisting of three sets of explosive single-leg jumps (20 for each leg) off a 30-cm box step alternating with three sets of high-resistance cycling sprints (5x 30 s at 60-70 min-1 with 30-s recovery between repetitions) on a magnetic braked training ergometer. Power output in the sprints was sampled using SRM cranks. Performance measures, obtained over 2-3 d on a Kingcycle ergometer before and after training, were mean power in a 1- and 4-km time trial, peak power in an incremental test, and lactate-profile power and oxygen cost determined from two fixed sub-maximal workloads. Results The control group showed little mean change in performance. Power output in the training sprints of the experimental group indicated a plateau in the training effect after 8-12 sessions. Relative to control the mean changes (±90% confidence limits) in the experimental group were: 1-km power, 8.7% (±2.5%); 4-km power, 8.1% (±4.1%); peak power, 6.8% (±3.6); lactate-profile power, 3.7% (±4.8%); and oxygen cost, -3.0% (±2.6%). Individual responses to the training were apparent only for 4-km and lactate-profile power (standard deviations of 2.5% and 2.8%). Discussion/Conclusion The addition of explosive strength training and high-resistance interval training to the programs of already well-trained cyclists produces major gains in sprint and endurance performance, partly through improvements in exercise efficiency and anaerobic threshold.